Political Generations and the Italian Environmental Movement(s): Innovative Youth Activism and the Permanence of Collective Actors. (October 2019) - Bertuzzi, Niccolò
During recent years, Italian social movements have experienced a period of crisis, in part due to diffuse antipolitical feelings and latent social conflict. However, environmental issues and especially territorial mobilizations remain relevant, due to the appearance of new contentious actors and to the permanence of long-standing organizations and important local grassroots campaigns. Based on 19 semistructured interviews with activists belonging to informal groups and formal associations, this article discusses the role of age and generations within the variegated Italian environmental archipelago, in which organizational and collective aspects prove to currently have a relevant role. Indeed, age does not represent an important fracture, representing a partial anomaly if confronted with the other case studies discussed in this special issue. The only diversities between cohorts are related to the forms of action preferred and (eventually) adopted, while the common perception of job precariousness among young activists is not translated into a single frame and common path of resistance. More than a Millennials' identity, it is rather appropriate to speak of various and divergent political generations: individuals belonging to different cohorts share some ideologies and visions of the world, especially related to territorial belongings or to specific ways of looking at environmental issues. Also for this reason, a final comparison between contemporary young activists and those of previous generations is proposed to address the generation(s) in movement(s) in a dynamic perspective.